Competitive rationality, the marketing concept and marketing strategy - Pitt, Leyland (Henry Stewart Talks, 2010)
Competitive Rationality, Managing Competitive Advantage as a Process, Customer Lifetime Value and Customer Equity, The Marketing Concept, Is the customer always right?, Defining the business, Marketing Strategy: The 4Cs and the 4Ps